Party System Dynamics in a Federal State. The Argentine Case - Altavilla, Cristian Daniel (2014)
This article analyzes evolution and change in the party system in Argentina. Starting from literature emphasizing the effects of territorialisation over the political party system, the article assesses the relevance of the territorial dimension as a key variable in party politics in Argentina. In order to describe this evolution and change, two variables are combined, one institutional and one capturing the material characteristics of the different constituencies. The focus of the analysis is purely national and, as a consequence, so are the parties which are its actors. The impact of territorialization is analyzed on the basis of their territorial organization and electoral performance over the past 30 years. After analyzing each party individually, the paper concludes with a discussion of the dynamics of the entire party system. The hypothesis is that the existence of different territories endowed with specific socioeconomic characteristics and political autonomy, combined with a particular electoral system and set of laws regulating party political structure, contributes to some extent to a heightened chance that party structures will fragment. All this translates into tension within the party structure something that could itself produce fragmentation within the party and, in more general terms, fragmentation of the entire party system.